2016
DOI: 10.1002/cam4.701
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of bevacizumab‐induced hypertension and clinical outcome in patients with colorectal cancer and lung cancer

Abstract: Bevacizumab(Avastin®), a humanized therapeutic monoclonal antibody that targets vascular endothelial growth factor, is widely used in cancer treatment. Patients who are treated with bevacizumab have an increased risk of developing systemic hypertension. However, the relationship between bevacizumab‐induced hypertension and clinical outcome remains unclear. We aimed to evaluate the effect of bevacizumab‐induced hypertension in terms of prognosis in patients with colorectal cancer and non‐small cell lung cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 17 publications
0
29
1
Order By: Relevance
“…Previous studies suggested that angiogenesis inhibitor-induced proteinuria is more likely to develop with colorectal cancer 15,19 . However, in the present study, there was no difference in the likelihood of proteinuria among cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that angiogenesis inhibitor-induced proteinuria is more likely to develop with colorectal cancer 15,19 . However, in the present study, there was no difference in the likelihood of proteinuria among cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Although AVEGF-HT might require anti-VEGF dose modification, withdrawal or treatment with antihypertensive drugs, it might also predict favourable survival outcomes in specific types of cancer, including renal cell carcinoma (RCC). 7 18 However, other studies have refuted this hypothesis. 19 , 20 Measurement of blood pressure (BP) in these studies was performed at different time points, using different protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there was a considerable variability in the criteria used for AVEGF-HT, which included ‘hypertension’ listed as diagnosis in medical records, the use of antihypertensive drugs, a predefined absolute BP increase from baseline, and on-treatment BP values above predefined thresholds. 7 17 , 19 – 21…”
Section: Introductionmentioning
confidence: 99%
“…More than 90% of the patients treated will experience a BP elevation, out of which 22–24% develop HTN any grade and 8% grade 3–4 [ 33 , 36 , 37 ]. It may occur at any time after the initiation of the treatment, most often being described after 1 month [ 30 ], or 3 months according to other authors (after 6 cycles) [ 38 ].…”
Section: Cardiovascular (Cv) Adverse Effects Of Bevacizumabmentioning
confidence: 99%